PENGEMBANGAN APLIKASI ISLAMIC EDUCATION FOR KIDS DALAM MENUMBUHKAN AKHLAQUL KARIMAH SISWA KELAS III SEKOLAH DASAR - Dheliati Fikriyah; Hanifah Aulia Rachmah; Trianti Khoerunnisa; Ani Nur Aeni (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Deviations in character in children today often occur. Various actions that do not reflect a good personality and even criminal acts committed by children are often found through television shows or social media. This of course needs to be followed up through character education. Character education in elementary schools has actually been carried out in school activities both through subjects and outside subjects with the aim of creating students who have noble character. At elementary school, games are very interesting for children. In addition, at elementary school age children begin to be interested in the use of electronic devices. In line with this, the application of Islamic Education for Kids is an appropriate medium to be used in character learning with the aim of improving the morals of students. The target users of this application are grade 3 elementary school students. The method used is the Design and Development (D&D) method. From the test results, users feel the benefits of this Islamic Education for Kids. By using this application, teachers can monitor and evaluate student learning outcomes through the features in the application